Akuntabilitas Dan Transparansi Laporan Keuangan Masjid (Studi Kasus Masjid Jogokariyan Yogyakarta) - Sabili, Faris; Romansyah, Dadang; Hidayat, Roni (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2023)
This research aims to reveal the problems of accountability and transparency in the financial statements of the Jogokariyan Mosque. The research method used is descriptive qualitative. The main source of research data was obtained through in-depth interviews with the management of the Jogokariyan Mosque. The results of the study indicate that the financial statements of the Jogokariyan Mosque have been presented in a transparent and accountable manner. In terms of accountability, it is evidenced by the existence of financial reports prepared by the mosque management, especially the treasurer in detail as a form of responsibility of the management to donors, in terms of transparency it is proven by the ease of access to financial information to worshipers and donors through mass media owned by the mosque in the form of information boards, websites. , and the Eid al-Fitr bulletin so that the funds received and utilized by the mosque are clearly recorded. Penelitian ini bertujuan untuk mengungkapkan masalah akuntabilitas dan transparansi dalam laporan keuangan Masjid Jogokariyan. Metode penelitian yang digunakan adalah kualitatif deskriptif. Sumber utama data penelitian diperoleh melalui wawancara mendalam dengan manajemen Masjid Jogokariyan. Hasil penelitian menunjukkan bahwa laporan keuangan Masjid Jogokariyan telah disajikan secara transparan dan akuntabel. Dalam hal akuntabilitas, terbukti dengan adanya laporan keuangan yang disiapkan oleh manajemen masjid, terutama bendahara secara rinci sebagai bentuk tanggung jawab manajemen kepada para donatur, dalam hal transparansi terbukti dengan mudahnya akses ke informasi keuangan bagi jamaah dan donatur melalui media massa yang dimiliki masjid berupa papan informasi, situs web, dan buletin Idul Fitri sehingga dana yang diterima dan digunakan oleh masjid tercatat dengan jelas.